ANALISIS STRATEGI PENERAPAN REKRUTMEN MANAJEMEN KINERJA ETOS KERJA DAN MOTIVASI KERJA PADA PEGAWAI KJKS BMT RIZQONA IKABU TAMBAKBERAS JOMBANG - Bekti Widyaningsih; Arivatu Ni’mati Rahmatika; Siti Fatihatul Ishlahiyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Sharia microfinance institutions act as economic facilitators for small and medium businesses and small traders, especially Baitul Maal Wat Tamwil (BMT). This research aims to determine the strategy for implementing employee recruitment, performance management, work ethic and work motivation at KSPPS BMT Rizkona IKABU Tambakbelas Jombang. This type of research uses a descriptive/qualitative approach to understand the events experienced by the subject and uses a verbal description method. Words and language. The research results show that: 1) The recruitment implementation strategy uses two methods, namely open and closed, and the implementation stages are: tests, interviews and training for one month, 2) The implementation of performance management is carried out in several month stages. BMT's goal (planning) phase, support phase in the form of accountability, evaluation phase, and reward phase. 3) Applicable work ethics. This means that employees should have a sense of responsibility and commitment to their work, and evaluations must be carried out once a month; 4) Work motivation must be increased so that work intentions are worship by affirming and motivating disciplinary goals through attendance. Act and serve with integrity.